Nodulação, aspectos bioquímicos, crescimento e produtividade do feijoeiro em função da aplicação de bioestimulante - Almeida, Adriana Queiroz de; Soratto, Rogério Peres [UNESP]; Broetto, Fernando [UNESP]; Cataneo, Ana Catarina [UNESP] (Univ Estadual Londrina, 2014)
The use of biostimulants can alter plant growth and development, but the action of they may be varied according to the stage of development of the plant. The aim was to evaluate the effects of forms and times of a biostimulant (cytokinin, indolebutyric acid, and gibberellic acid) application on nodulation, some biochemical aspects, growth and yield of common bean cultivar Perola. The treatments were: Control (without application); TS - 250 mL ha(-1) seed treatment; V-4 - 250 mL ha(-1) foliar spray in V-4 stage; R-5 - 250 mL ha(-1) foliar spray in R-5 stage; TS+V-4 - 250 mL ha(-1) in TS + 250 mL ha(-1) in V-4; TS+R-5 - 250 mL ha(-1) in TS + 250 mL ha(-1) in R-5; V-4+R-5 - 250 mL ha(-1) in V-4 + 250 mL ha(-1) in R-5, and TS+V-4+R-5 - 250 mL ha(-1) in TS + 250 mL ha(-1) in V-4 + 250 mL ha(-1) in R-5. The foliar biostimulant application in the vegetative (V-4) or early reproductive phase (R-5) increases nodulation, root growth, content of soluble sugars, content of total amino acid and nitrate reductase activity, however, does not interfere with shoot growth and grain yield of common bean.
Nodulation, biochemical aspects, growth and yield of common bean according biostimulant application
Keywords: Phaseolus vulgaris; plant regulator; nitrate reductase; root growth